Investigation mechanisms of action and resistance of Edwardsiella ictaluri to trans-cinnamaldehyde - Hossam Abdelhamed; Munshi Mustafiz Riman; Mark A. Arick; Ali Sobhy Dawood; Basant Gomaa; Monzur Chowdhury; Larry A. Hanson; Attila Karsi (PLoS ONE, 2026)
The rise of multidrug-resistant (MDR) pathogens in aquaculture poses a significant threat to food safety and public health by facilitating the transfer of resistance across the food chain, underscoring the need for sustainable, non-antibiotic control measures. Trans-cinnamaldehyde (TC), a phytochemical with antimicrobial activity, is a promising alternative. While previous publications have established the antibacterial efficacy of TC against Edwardsiella ictaluri , the agent of enteric septicemia of catfish, its mechanism of action and the potential for bacterial adaptation after prolonged exposure remain undefined. Here, we addressed these gaps by investigating the antibacterial mechanism, the adaptive response of E. ictaluri to TC, and the vaccine potential of TC-adapted strains, with relevance to One-Health. The minimum inhibitory concentration (MIC) of TC against E. ictaluri was 120 µg/mL, whereas 16 µg/mL was not inhibitory and was used for long-term adaptation. Serial passages for 30 and 60 days generated D30- and D60-adapted strains. Disk diffusion assays indicated reduced susceptibility to TC and florfenicol but increased susceptibility to sulfamethoxazole/trimethoprim (SXT) in adapted strains. Virulence assays in catfish fingerlings (three tanks containing 10 fish per tank) demonstrated that D30-TC and D60-TC strains were highly attenuated. Moreover, vaccination with these strains conferred significant protection against wild-type challenge (63.64% and 73.64% survival compared to 20% in controls). Quantitative proteomics revealed the upregulation of multidrug efflux pumps and stress adaptation proteins and the downregulation of central metabolic pathways during TC exposure. Long-term adaptation was characterized by metabolic reprogramming, including enhanced energy and carbohydrate metabolism and suppression of virulence-associated secretion systems. Comparative genomics of D30-TC and D60-TC strains revealed shared mutations in genes related to membrane biosynthesis, energy metabolism, stress response, and regulatory pathways. Together, these findings highlight the potential of TC as an antimicrobial and a potential source of live-attenuated vaccine, while revealing adaptive mechanisms that may inform future strategies for controlling E. ictaluri infections.